A 44-Year-Old Man with Waldenstrom Macroglobulinemia and Bilateral Maxillary Sinusitis - Shinta Oktya Wardhani; Herman Bagus Trianto; Muhammad Anshory (Acta Medica Indonesiana)
Waldenstrom macroglobulinemia is a chronic, indolent, lymphoproliferative disorder, which is characterized by the presence of a high macroglobulin (IgM) level, elevated serum viscosity, and the presence of a lymphoplasmacytic infiltrate in the bone marrow. Clinical manifestations may be found due to the presence of IgM paraprotein and malignant lymphoplasmacytic cell infiltration of the bone marrow and other tissues. We reported a case of male patient with Waldenstrom macroglobulinemia and bilateral maxillary sinusitis. He had received symptomatic and antibiotic treatment for his sinusitis, FFP and PRC transfusion to improve his general condition and chemotherapy with CHOP regimen as definitive treatment.